Finite element models for nonlinear analysis of onshore wind turbines’ embedded-ring foundations - DOURADO, Thaís Tenório (2022)
Wind turbines’ share in the energy industry continues to grow, its renewable energy source status deeming it attractive due to environmental policies established worldwide. Most of these turbines are onshore installations and are supported by steel towers connected to reinforced concrete foundations through embedded rings, a type of structure with reported damages to the tower-foundation interface. This study presents simulation procedures for this kind of foundation concerning their structural behaviour. Emphasis is given to developing finite element models with the aid of the finite element software Abaqus. Four 3D models were developed with differing numerical assumptions so that it would be possible to understand how each affected the structural behaviour and which model better fitted the purpose of investigating the concrete around the bottom flange of the steel ring. The assumptions cover nonlinear elastic supports, contact interaction and nonlinear concrete behaviour. This research provides a valuable resource since the knowledge of the structural response of the different assumptions led to the design of a numerical model capable of reproducing some field-reported behaviours in the foundation. This model can be used to prevent deterioration in embedded-ring foundations, and future advances can guide maintenance and rehabilitation plans on existing wind turbine farms.